Project on Human Development in Chicago Neighborhoods (PHDCN): School Interview, Wave 3, 2000-2002 - Earls, Felton J. ([Verlag nicht ermittelbar], 2007)
The Project on Human Development in Chicago Neighborhoods (PHDCN) was a large-scale, interdisciplinary study of how families, schools, and neighborhoods affect child and adolescent development. One component of the PHDCN was the Longitudinal Cohort Study, which was a series of coordinated longitudinal studies that followed over 6,000 randomly selected children, adolescents, and young adults, and their primary caregivers over time to examine the changing circumstances of their lives, as well as the personal characteristics, that might lead them toward or away from a variety of antisocial behaviors. Numerous measures were administered to respondents to gauge various aspects of human development, including individual differences, as well as family, peer, and school influences. One such measure was the School Interview protocol. This was adapted from the school section of the Youth Interview Schedule used in the Philadelphia Family Management Study. It included sections addressing school climate, school safety, types of classes the subject had taken, the subject's attitude toward school, and participation in activities within and outside of school and in after-school activities. It was administered to subjects in Cohorts 6, 9, and 12. It is closely related to PROJECT ON HUMAN DEVELOPMENT IN CHICAGO NEIGHBORHOODS (PHDCN): SCHOOL INTERVIEW, WAVE 2, 1997-2000 (ICPSR 13654).